1983
DOI: 10.1136/adc.58.10.799
|View full text |Cite
|
Sign up to set email alerts
|

A common congenital immunodeficiency predisposing to infection and atopy in infancy.

Abstract: SUMMARY Twenty six infants with a congenital immunodeficiency, characterised by failure of their sera to opsonise heat killed bakers' yeast for phagocytosis by normal polymorphonuclear leucocytes, were studied during infancy to determine the frequency of infection and development of atopy. They were compared with controls, matched prospectively for birth date, sex, parental smoking, and atopy and in whom feeding patterns were similar. In 18 of 26 infants the serum defect persisted at age one year. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 11 publications
4
34
2
1
Order By: Relevance
“…A period of vulnerability between 6 and 18 months of age has been proposed in which MBP may play a significant role in innate defense [13 14,18]. This hypothesis is supported by earlier studies associating the common opsonic defect with infection and atopy in infancy [19,20]. On the other hand, a survival advantage for low MBP levels is suggested by the high frequency of mutant alleles which result in low MBP levels [14][15][16], and both the biological and clinical significance of MBP is still to be determined.…”
Section: Introductionmentioning
confidence: 71%
“…A period of vulnerability between 6 and 18 months of age has been proposed in which MBP may play a significant role in innate defense [13 14,18]. This hypothesis is supported by earlier studies associating the common opsonic defect with infection and atopy in infancy [19,20]. On the other hand, a survival advantage for low MBP levels is suggested by the high frequency of mutant alleles which result in low MBP levels [14][15][16], and both the biological and clinical significance of MBP is still to be determined.…”
Section: Introductionmentioning
confidence: 71%
“…The studies which have shown association between low MBL serum level and recurrent infections have been performed in children hospitalized for a variety of infections including serious invasive infections, and the controls have consisted of children staying in hospital for other reasons (Richardson et al 1983, Super et al 1989, Summerfield et al 1997. Thus, low MBL serum levels may still be associated with infections in children with other immunological disorders as suggested by Garred et al (1995) and infections in children with low MBL serum levels may be more virulent and cause more frequent hospital admittance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a high frequency of the promotor gene variant haplotype HY = 0.83 in Eskimos, the median serum MBL levels in persons homozygous for normal MBL alleles are 2.5 to 5 times higher in East Greenlanders than in Europeans and Africans (Garred et al 1992. Absent or low MBL serum concentrations have been associated with recurrent infections in early childhood in hospitalized children and in immunodeficient patients (Richardson et al 1983, Super et al 1989, Summerfield et al 1997. It has also been suggested that high MBL levels are associated with certain infections caused by intracellular parasites such as Mycobacterium leprae, Mycobacterium tuberculosis, Legionella pneumophilia, and certain viruses such as herpes simplex type 2 (Fischer et al 1994.…”
Section: Aimsmentioning
confidence: 99%
“…A common complement-dependent opsonic defect found with increased frequency in children with recurrent upper airway infections, including OM, and diarrhea during infancy [31,32] has been shown to be caused by low concentration of mannose-binding protein (MBP) [33]. Allelic variants of MBP associated with low concentrations of MBP have been seen with mutations in codon 54 and 57 [33,34].…”
Section: Immune Mechanismsmentioning
confidence: 98%